Morphological and Morphometrical Studies on the Scapula of Himalayan Mongoose - R. Rajput, (Indian Journal of Veterinary Anatomy, 2022)
The Himalayan mongoose is a brown mongoose species native to the Himalayan region of Indiansubcontinent. The paintbrushes we use are generally made from Mongoose hairs. The specimen under study wascollected from an animal that was hit by a moving car in Palampur. The specimen was preserved and the dissectionwas done to record the anatomical observations on the scapula of Himalayan mongoose. The scapula wasquadrangular in shape with two surfaces, three borders and three angles. The maximum length and width ofscapula were 4.52cm and 2.39 cm respectively. The lateral surface was divided into two fossae by a welldeveloped,3.23 cm long scapular spine. The ratio of supraspinatus to infraspinatus fossae was 1.32: 1.00. The subscapular fossa was shallow. The cranial border was convex whereas, the caudal border was straight. The cranial angle was not distinct and it merged with the adjacent borders, whereas the caudal angle was distinct, thick, rough and tuberous.The spine of scapula ended distally as hamate process and a distinct supra-hamate process wasnoticed.